EFEK LARVISIDAL EKSTRAK ETER RIMPANG LEMPUYANG GAJAH (ZINGIBER ZERUMBET) TERHADAP LARVA NYAMUK AEDES AEGYPTI - , IMAM MUKTIADI; , dr. Tri Baskoro Tri Satoto, MSc, Phd ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Aedes aegypti is the main vector of dengue fever in South East Asia. Interrupting the life cycle of the vector is main strategy to reduce the incidence of filariasis. The breeding of the mosquito is cut down by larvicide, especially synthetic larvicide. This causes problems especially when synthetic larvicide is applied uncontrollably. The problems consist of vector resistance and environmental pollution. Therefore, it is essential to search for alternative larvicide, for instance Zingiber zerumbet as natural larvicide. Objectives. To explore larvicidal effect of Zingiber zerumbet roots with eter extract. To find out LC50 and LC90 of the extract against 3rd/4th instar larvae of Aedes aegypti. To find out the relation between variety of the extract dose and larvae mortality. Methods. This research is quasi experimental study using WHO 2005 guidance. 3rd/4th instar larvae divided into 6 treatment groups and 1 control group. Each group contains 10 larvae with 3 times replication in 100 ml solution. Larvae mortality was counted after 24 hours of exposure and the data was analyzed using probit analysis. Result. LC50 and LC90 values were 51.45925 ppm and 158.8763 ppm. The probit regression line obtained is Y = -2.27 + 3.91X. Conclusion. Eter extract of Zingiber zerumbet roots has larvacidal activity against 3rd/4th instar of Aedes aegypti larvae. LC50 and LC90 values were 51.45925 ppm and 158.8763 ppm. The increasing dose of the extract increases larvae mortality. Keyword: Aedes aegypti, Zingiber zerumbet, botanical larvicide, probit analysis